2014
DOI: 10.1186/preaccept-4336743301397410
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis in Malawi: a systematic review

Abstract: Introduction: Schistosomiasis remains an important public health problem that undermines social and economic development in tropical regions of the world, mainly Sub-Saharan Africa. We are not aware of any systematic review of the literature of the epidemiology and transmission of schistosomiasis in Malawi since 1985. Therefore, we reviewed the current state of knowledge of schistosomiasis epidemiology and transmission in this country and identified knowledge gaps and relevant areas for future research and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…Given the large differences in smoking prevalence between men and women in this country (ie, 26.3% and 6.3% in men and women, respectively) [44], other risk factors may be in operation. However, the evidence for a role of schistosomiasis in Malawi remains limited [45].…”
Section: Discussionmentioning
confidence: 99%
“…Given the large differences in smoking prevalence between men and women in this country (ie, 26.3% and 6.3% in men and women, respectively) [44], other risk factors may be in operation. However, the evidence for a role of schistosomiasis in Malawi remains limited [45].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in Phalombe and along the shore areas of Lake Malawi reported a prevalence of about 94% in school aged children [8]. Consequently, studies on schistosomiasis in Malawi have been either conducted along Lake Malawi shores or concentrated in same places only [9,10]. This approach has resulted in leaving out all potential endemic areas, which include water reservoirs that serve a large proportion of the country's population.…”
Section: Introductionmentioning
confidence: 99%
“…In Malawi, there are about 750 water reservoirs, with only 7 large dams mainly for municipal water supply [11]. Furthermore, the approach has rendered schistosomiasis information fragmented such that it difficult to make a correct conclusion on the distribution and transmission of the disease in Malawi [9]. The present study was conducted to investigate the role of water reservoirs in transmission and prevalence of schistosomiasis in Malawi to provide and improve knowledge of schistosomiasis in Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…Human schistosomiasis is one of the most prevalent and serious parasitic diseases in tropical and subtropical regions [ 1 ]. It affected approximately 200 million people worldwide.…”
Section: Introductionmentioning
confidence: 99%